Antibacterial, antibiofilm and cytotoxic activities of Terminalia fagifolia Mart. extract and fractions - Araujo, Alyne Rodrigues de (2015)
Background: The methicillin resistance of bacteria from the genus Staphylococcus and its ability to form biofilms are important factors in pathogenesis of these microorganisms. Thus, the search for new antimicrobials agents, especially from plants, has been intensified. In this context, Terminalia species have been the subject of research for many pharmacological activities. In this study we evaluated the antibacterial, antibiofilm and cytotoxic activities of the ethanol extract (EtE) from Terminalia fagifolia stem bark as well as that of three fractions of the extract (AqF, HaF and WSF). Methods: We determined the minimum inhibitory concentration (MIC) by microdilution in 96-well plates, where the strains were exposed to serial dilutions of the ethanol extract and fractions, ranging from 12.5 to 400 μg/mL. We then determined the minimum bactericidal concentration (MBC), seeding the inoculum (10 μL) with concentrations equal to or greater than the MIC in Mueller-Hinton agar. To test the antibiofilm activity biofilm formation was induced in the presence of concentrations equivalent to 1/2, 1/4 and 1/8 of the MIC extract or fraction tested. In addition, the effect of the EtE and the fractions on cell viability was tested by the MTT assay on human MCF-7 breast cancer and mouse fibroblast NIH/3T3. To obtain high-resolution images of the effect of the aqueous fraction on the bacterial morphology, atomic force microscopy (AFM) imaging of treated S. aureus cells was performed. Results: We observed antibacterial activity of EtE and fractions with MICs ranging from 25–200 μg/mL and MBCs ranging from 200–400 μg/mL. Regarding antibiofilm activity, both the EtE as the AqF, HaF and WSF fractions showed significant inhibition of the biofilm formation, with inhibition of biofilms formation of over 80% for some strains. The EtE and fractions showed a moderate cytotoxicity in cell line NIH/3T3 viability and potential antitumoral activity on human breast cancer cell line MCF-7. The microscopic images obtained revealed morphological changes to the S. aureus ATCC 29213 surface caused by AqF, as well as significant size alterations. Conclusions: The results show potential antibacterial, antibiofilm and antitumoral activities of the ethanol extract and fractions of T. fagifolia.